New treaty, new tradition: reconciling New Zealand and Maori law - Jones, Carwyn (UBC Press, 2016)

Tupuna Awa: People and Politics of the Waikato River - Muru-Lanning, Marama (Auckland University Press, 2016)
'We have always owned the water . . . we have never ceded our mana over the river to anyone', King Tuheitia Paki asserted in 2012. Prime Minister John Key disagreed: ‘King Tuheitia's claim that Maori have always owned New Zealand's water is just plain wrong'. So who does own the water in New Zealand – if anyone – and why does it matter? Offering some human context around that fraught question, Tupuna Awa looks at the people and politics of the Waikato River. For iwi and hapu of the lands that border its 425-kilometre length, the Waikato River is an ancestor, a taonga and a source of mauri, lying at the heart of identity and chiefly power. It is also subject to governing oversight by the Crown and intersected by hydro-stations managed by state-owned power companies: a situation rife with complexity and subject to shifting and subtle power dynamics. Marama Muru-Lanning explains how Maori of the region, the Crown and Mighty River Power have talked about the ownership, guardianship and stakeholders of the river. By examining the debates over water in one New Zealand river, over a single recent period, Muru-Lanning provides a powerful lens through which to view modern iwi politics, debates over water ownership, and contests for power between Maori and the state.
Keywords: iwi politics; water ownership

Indigenous Data Sovereignty: Toward an agenda - Kukutai, Tahu (ANU Press, 2016)
As the global ‘data revolution’ accelerates, how can the data rights and interests of indigenous peoples be secured? Premised on the United Nations Declaration on the Rights of Indigenous Peoples, this book argues that indigenous peoples have inherent and inalienable rights relating to the collection, ownership and application of data about them, and about their lifeways and territories. As the first book to focus on indigenous data sovereignty, it asks: what does data sovereignty mean for indigenous peoples, and how is it being used in their pursuit of self-determination? The varied group of mostly indigenous contributors theorise and conceptualise this fast-emerging field and present case studies that illustrate the challenges and opportunities involved. These range from indigenous communities grappling with issues of identity, governance and development, to national governments and NGOs seeking to formulate a response to indigenous demands for data ownership. While the book is focused on the CANZUS states of Canada, Australia, Aotearoa/New Zealand and the United States, much of the content and discussion will be of interest and practical value to a broader global audience.
Keywords: data; data sovereignty; indigenous data sovereignty

Here to stay: Reshaping the regions through mana Māori - Kukutai, Tahu; Simmonds, Naomi Beth; Ryks, John (Massey University Press, 2016)
Situated 65 kilometres south-east of Hamilton, Putāruru (population 3747 in the 2013 Census) is typical of the many farming service towns scattered across rural Aotearoa New Zealand. Bakeries, op shops, a sports bar and a farm equipment supplier occupy the main street. Unlike nearby Tirau, which transformed from a one-stop shop into a vibrant boutique village in the late 1990s, Putāruru township remains largely indistinguishable from other rural centres. There are few clues to the substantial farming-based and water-generated wealth that lies beyond the town.
Keywords: economic aspects; mana whenua; tino rangatiratanga